Newair / Muhammad Haiman Aminuddin - Aminuddin, Muhammad Haiman (2022)
This an attempt to know how the theories can be applied to practical situation. As a student in UiTM Arau, it is a part of study for everyone to undergo a case study project. So, for this purpose, we got the opportunity to research a company which manufactured the same product that we want to develop, which is NewAir ice maker company, currently based in California. In the first part of the project report, the general information of the company has been collected. Information is gathered through the primary and secondary source as well. In the second part of the report, contains the specialized subject study. Objective of the project is to work on the background, organizational structure, products, and services that NewAir provides. Next, we study about the technology of NewAir ice maker, which is basically a normally technology used by the refrigerator in freezer section, as well as business, marketing and its operational strategy used by the company to promote their products which we find quite interesting. Goals indicate what a business unit wants to achieve. Strategy is an action plan for getting the goals. Every business must design a strategy for achieving its goals, consisting of a marketing strategy, and an effective management. In this case study, we analysed the strength, weaknesses, opportunities, and threats of this company in real business world by using SWOT analysis. Thus, from the needs and demands form the existing consumers of this company, we analysed and find a solution to overcome and to fulfil their needs in Consumer Trend Canvas (CTC) analysis, making it as our innovation to be continued in new Product Development task.